Practical Use of Triangle Block Model for Bridging between Problem and Solution in Arithmetic Word Problems (International Conference on Computers in Education, 2016)
This paper reports a practical use of triangle block model for learning of arithmetic word problems. The triangle block model has been proposed as a bridging model between conceptual representation of a word problem and quantitative representation of its solution. Based on this model, we have developed an interactive environment where a pupil is able to manipulate an integrated representation of the conceptual and quantitative ones as learning of arithmetic word problems. We also designed a series of lessons to use the environment. The lessons were practically conducted for 75 4th grade pupils (in two classes) in an elementary school for 7 class times. As the results, it was confirmed that (1) the pupils and their responsible teacher accepted the lessons as useful ones, and (2) the lessons had learning effect as improvement of structural understanding for the problems.